The Effect of Problem-Based Learning on Students’ Adversity Quotient - Cep Riri Irawan; Carsiwan Carsiwan; Tri Martini (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Physical Education (PE) plays a vital role in developing students' physical and mental capabilities, including their Adversity Quotient (AQ) in facing challenges. This two-cycle Classroom Action Research (CAR) aims to examine the effect of a Problem-Based Learning (PBL) model in floor gymnastics on students' AQ. A total of 41 eleventh-grade students from class XI-2 at SMAN 10 Bandung were selected using a purposive sampling technique. Data were collected through AQ questionnaires, observation sheets, and skill tests, and subsequently analyzed using a paired t-test and reflective analysis. The results indicated that the PBL model exerted a significant positive effect on students' AQ, marked by an increase in the mean score from 64.54 to 73.61. Nonetheless, a mean N-Gain value of 0.2453 (low) and an effectiveness percentage of 24.52% (ineffective) indicated that the rate of improvement progressed slowly on a small scale. In conclusion, the PBL model in PE simultaneously has the potential to intervene in students' psychological aspects. The PBL model is empirically proven to transform students' mental resilience profiles through massive vertical migration, in which the number of students in the Quitter category (easily giving up) was successfully reduced to 0%, while the proportion of students in the Climber category (resilient fighters) surged sharply from 7% to 37%. However, to achieve an optimal increase in AQ, a consistent application of the model over a longer period is required, accompanied by the modification of safe instructional tools.